Influencia de la ganadería en la evolución del riesgo de incendio en función de la vegetación en un área de montaña: el ejemplo del valle de Borau (Pirineo aragonés) - Pérez González, María Eugenia; Sanz Donaire, Juan José (Geographicalia, 2016)
This paper wants to expose the different statistical distributions of the annual rainfall time series in Spain. Data used were those published by the I.N.M. in 1996, as we consider that, even with the risk of managing some not homogeneous series, these are the only real data and, analyzed for the whole territory of Spain, they can throw light, in most of the cases, upon the behaviour of rainfall. The different statistical rainfall distributions in Spain allow us to know the frequency of the driest and more humid periods that control some socioeconomic tasks. Other statistical well-known values will be calculated and compared to "normal" values, according to the concept of climate proposed by one of the authors.
Keywords: statistical distributions; annual rainfall; long time series; Spain